Emprego do etanol como substituto ou adjuvante do ácido sulfúrico no tratamento das células em fermentação alcoólica contaminada por Lactobacillus fermentum - Neto, José Machado da Silva (2019)
Bacterial contamination is one of the major factors to cause decrease in the fermentative efficiency in the process of bioethanol production. To control the growth of bacterial contaminants, Brazilian industries utilize the acid treatment (sulfuric acid solution at pH 2.0) between the fermentative cycles. When the acid treatment is not effective, biocides and antibiotics are added which result in cost and antibiotic resistance in bacteria. In this context, this work aimed initially to evaluate the effect of ethanol on the growth of the bacterium Lactobacillus fermentum in Man-Rogosa-Sharpe (MRS) medium, following the evaluation of using ethanol as substitute or adjuvant (which enhances the action) of the sulfuric acid in the cell treatment during the alcoholic fermentation to control the growth of this bacterium. The effect of the treatment pH 2.0 + 5% ethanol switching with the treatment pH 2.0 in cell-recycled batch fermentation carried out in non-sterile must with an industrial strain of Saccharomyces cerevisiae (PE-2) and contaminated with L. fermentum was also verified. Fermentative parameters and the microorganism growth were determined. A decrease in the maximal specific growth rate and an increase in the lag phase of L. fermentum were observed in culture medium with ethanol up to the concentration of 14% v/v. Concerning the cell treatments, there was total loss of cell viability of L. fermentum in the treatments pH 2.0 + 5% ethanol, pH 3.0 + 20% ethanol and hydroalcoholic solution with 22% ethanol. Inhibition of ethanol production, decrease of two log cycles in the number of S. cerevisiae and total loss of cell viability of L. fermentum were observed when the cell treatment was carried out in the hydroalcoholic solution with 22% ethanol, then a non-viable treatment to be utilized in the industry. The logarithmic variation in the number of CFU/mL was much lower than 1 log cycle up to 15% ethanol as well as for the treatments with pH higher than 2.0 with or without ethanol. The switching of cell treatments pH 2.0 + 5% ethanol and pH 2.0 without addition of ethanol during the fermentative cycles was effective when the contamination of the non-sterile must with L. fermentum was not high, because the loss of cell viability of this bacterium was only possible with the treatment pH 2.0 + 5% ethanol. The yeast S. cerevisiae was not affected by the use of the treatment pH 2.0 + 5% ethanol and the highest alcoholic concentrations in the must were obtained when ethanol was added to the acid treatment. We conclude that the ethanol is an adjuvant and not a substitute of the sulfuric acid for the growth control of L. fermentum, standing out the cell treatment pH 2.0 + 5% ethanol as the most economic and effective.